The Influence of Intellectual Intelligence and Emotional Intelligence on Student Discipline in Learning Islamic Education at SMP Negeri 2 Parepare - Zulfiah, Zulfiah; Hamdanah, Hamdanah (IAIN Parepare, 2021)
This study discusses the effect of intellectual and emotional intelligence on student discipline in Islamic education for Class VIII SMP Negeri 2 Parepare. This study aims to determine the effect of intellectual and emotional intelligence on students’ discipline in learning Islamic education class VIII SMP Negeri 2 Parepare. This study uses a quantitative approach, with a correlational research type with multiple linear regression. The number of samples in this study was 110 students, while data collection used observation, questionnaire and documentation methods, then analyzed descriptively and inferentially. The results showed, 1) The level of Intellectual Intelligence of Class VIII students of SMP Negeri 2 Parepare was included in the above average category based on Alfred Bine’s IQ classification with a value of 110. While the Emotional Intelligence Level of Class VIII students of SMP Negeri 2 Parepare was included in the category the results obtained from the study 6439: 7920 = 81.3%. 2) Discipline Level of Class VIII Students of SMP Negeri 2 Parepare is included in the high category from the research results 6007: 7040 = 85.3%. 3) Intellectual Intelligence and Emotional Intelligence together significantly influence the discipline of learners in the learning PAI in Junior High School 2 of Pare Pare with a value of F count 22.732> F table3.08 so that it has a significant effect with the coefficient of determination obtained by 0.298 or 29.8% , which means that the contribution of the intellectual and emotional intelligence variables is 29.8% and 70.2% is influenced by other factors which are not examined in this study